How to reduce discrimination? Evidence from a field experiment in amateur soccer - Robert Dur; Carlos Gomez-Gonzalez; Cornel Nesseler (Tinbergen Institute, 2022)
A rich literature shows that ethnic discrimination is an omnipresent and highly persistent phenomenon. Little is known, however, about how to reduce discrimination. This study reports the results of a large-scale field experiment we ran together with the Norwegian Football Federation. The federation sent an email to a random selection of about 500 amateur soccer coaches, pointing towards the important role that soccer can play in promoting inclusivity and reducing racism in society and calling on the coaches to be open to all interested applicants. Two weeks later, we sent fictitious applications to join an amateur club, using either a nativesounding or a foreign-sounding name, to the same coaches and to a random selection of about 500 coaches who form the control group. In line with earlier research, we find that applications from people with a native-sounding name receive significantly more positive responses than applications from people with a foreign-sounding name. Surprisingly and unintentionally, the email from the federation substantially increased rather than decreased this gap. Our study underlines the importance of running field experiments to check whether well-intended initiatives are effective in reducing discrimination.
Keywords: C93; J15; Z2; 330; ethnic discrimination; intervention; field experiment; correspondence test; amateur soccer